Estimation of Serum Uric Acid Level in Preeclamptic Women Determine the Severity of Preeclampsia - Nahar, Khairun; Khatun, Sayada Fatema; Khan, Naila Atik (Anwer Khan Modern Medical College Journal, 2020)
Background: Serum uric acid is a relatively insoluble metabolite of purine metalolism which is mainly secreted by the kidneys and the rate is dependant on renal blood flow. It increases in preeclampsia and studies show it may be a marker of severe preeclampsia. Objective: To determine the serum uric acid level in preeclampsia, to compare the serum uric acid level between mild and sever preeclampsia and to find out any relationship of the serum uric acid level with hypertension in preeclampsia. Methods and materials: This cross sectional study was conducted in Dhaka Medical College Hospital in eclampsia ward of Gynae & Obs department during the period from January 2010 to December 2011. This study group composed of 92 diagnosed case of preeclampsia patient. Out of the 92 cases, 42 were mild preeclampsia and 50 were severe preeclampsia. Result: The results of the study showed that the mean serum uric acid level was significantly high in severe preeclampsia compared to mild preeclampsia and there is a positive and significant relationship of serum uric acid level with hypertension in preeclampsia. Conclusion: There is significant association between serum uric acid level and hypertension in Preeclampsia. Anwer Khan Modern Medical College Journal Vol. 11, No. 1: Jan 2020, P 35-40